Estimasi sudut orientasi rigid body dengan menggunakan sensor IMU (Inertial Measurement Unit) dan Magnetometer - Sandi, Briyan Yoga; Kurniawan, Freddy; Lasmadi, Lasmadi (SENATIK STT Adisutjipto, 2020)
One of the instruments that can be used today for navigation is the IMU (Inertial Measurement Unit) sensor which consists of an accelerometer sensor, gyroscope, and an additional magnetometer. The three sensors are useful for determining the orientation angle. However, the presence of high enough noise in the three-output data can cause the orientation angle to be inaccurate. This study aims to determine the roll, pitch and yaw orientation more accurately using a Kalman filter. This filter is used because it has a lightweight computation and can reduce noise significantly. The results of this study show that the orientation angle calculated using the Kalman filter is close to the actual orientation angle with an accuracy of 99.2% for roll, 99.5% for pitch, and 98.6% for yaw.